Liposomes as a Promising Ultrasound-Triggered Drug Delivery System in Cancer Treatment - Salkho, Najla (2017)
The initial uses of ultrasound waves in the medical field were limited to the thermal ablation of solid tumors and as a diagnostic tool. Recent advances at the preclinical stage have allowed the use of ultrasound as a powerful tool to improve drug delivery when the agent is administered encapsulated inside a nanoparticle. This spatial and temporal control of drug release, using a non-invasive modality, is a promising approach to decrease the side effects of conventional chemotherapy in cancer treatments, as it reduces the interaction of the anti-neoplastic agent with healthy tissues. In this review, we explain the physics of ultrasound, introduce and discuss several examples on the use of nanoparticles as drug carriers, with a focus on liposomes. Examples of in vitro and in vivo studies are presented and discussed.